Leadership in middle management and operations - Loch, Christoph H. (Henry Stewart Talks, 2012)
The connection between top strategy and front line operations, Strategy cascading through goals and actions, The paradox of leadership at the mid level, The emotional roots and double sides of leadership, The benefits and risks of leadership for groups, Leadership skills and behaviour at the front line